2016
DOI: 10.3109/13880209.2016.1160251
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacology, toxicology and potential applications of arecoline: a review

Abstract: Context: Arecoline is an effective constituent of Areca catechu L. (Arecaceae) with various pharmacological effects. However, investigations also revealed that long use of arecoline could arouse some oral diseases. Objective: The present review gathers the fragmented information available in the literature (before 1 October 2015) regarding pharmacology and toxicology of arecoline. We also discussed the potential developments and applications of arecoline in the future. Methods: All the available information re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 71 publications
3
67
0
Order By: Relevance
“…Thereafter, in vivo and in vitro bioassays are used to screen the change in bioactivity. Based on our preliminary experimental results (Supplementary files Figures S1 and S2) and related references1920, arecoline is the main alkaloid among the total alkaloids of CAN extracted by CHCl 3 . Importantly, we also found that there was no other obvious constituent that interfered in the same position as the arecoline band (Figure S2).…”
Section: Discussionmentioning
confidence: 92%
“…Thereafter, in vivo and in vitro bioassays are used to screen the change in bioactivity. Based on our preliminary experimental results (Supplementary files Figures S1 and S2) and related references1920, arecoline is the main alkaloid among the total alkaloids of CAN extracted by CHCl 3 . Importantly, we also found that there was no other obvious constituent that interfered in the same position as the arecoline band (Figure S2).…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, although the parasympathomimetic arecoline has been thought to be responsible for most of the effects of betel quid chewing, studies have shown that plasma concentrations of noradrenaline and adrenaline were elevated, suggesting an additional sympathetic activation [64]. In folk medicine, chewing betel nut is considered to enhance the memory [66]. However, use of betel nut is also related to palpitation, oral submucous fibrosis, oral squamous cell carcinoma, and genotoxicity.…”
Section: Arecolinementioning
confidence: 99%
“…However, use of betel nut is also related to palpitation, oral submucous fibrosis, oral squamous cell carcinoma, and genotoxicity. Arecoline is reported to be the primary toxic constituent responsible for these effects [65,66].…”
Section: Arecolinementioning
confidence: 99%
“…AN extract (ANE) can induce the generation of reactive oxygen species (ROS) in both saliva and solution, as well as the modification of DNA [2,3]. The major alkaloid of AN, arecoline, is capable of causing oral submucous fibrosis (OSF), oral squamous cell carcinoma (OSCC) and genotoxicity [4]. Moreover, arecoline and another AN ingredient, oligomeric procyanidins, are known to trigger cellular apoptosis [5,6].…”
Section: Introductionmentioning
confidence: 99%